Resolva as questões no método de substituição: 3x = y / 2x - 3y = 7
Soluções para a tarefa
Respondido por
6
3x=y
x= y/3
2x-3y=7
2*(y/3)-3y=7
(2y/3)-3y=7
igualando os denominadores:
2y-9y=21
-7y=21 * (-1)
7y=-21
y=-21/7
y= -3
x=y/3
x= -3/3
x= -1
x= y/3
2x-3y=7
2*(y/3)-3y=7
(2y/3)-3y=7
igualando os denominadores:
2y-9y=21
-7y=21 * (-1)
7y=-21
y=-21/7
y= -3
x=y/3
x= -3/3
x= -1
Perguntas interessantes
História,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás